Effects of heat treatment time on electrochemical properties and electrode structure of polytetrafluoroethylene-bonded membrane electrode assemblies for polybenzimidazole-based high-temperature proton exchange membrane fuel cells - Kim, MinJoong; Jeong, GiSu; Eom, KwangSup; Cho, EunAe; Ryu, JoungWook; Kim, Hyoung-Juhn; Kwon, HyukSang (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
To improve cell performance, the effects of heat treatment time on the electrochemical properties and electrode structure of PTFE-bonded membrane electrode assemblies for PBI-based high-temperature proton exchange membrane fuel cells are investigated. The cell performance is observed to decrease in the high-current-density region rather than in the low-current-density region with increasing heat treatment time at 350 degrees C from 1 to 30 min. Microscopic studies reveal remarkable differences in the electrode structure by the agglomeration of dispersed PTFE and adjacent catalyst particles, depending on the heat treatment time. As the heat treatment time increases, only the large pore (secondary pore) volume in the electrode decreases, resulting in increase in mass transport resistance and concentration overpotential in the high-current-density region. Cell performance is not measured without heat treatment because the electrodes are not formed. When the electrodes are heat treated for 1 min at 350 degrees C, the best cell performance is obtained, 0.67 V at 200 mA cm(-2). Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ACID-DOPED POLYBENZIMIDAZOLE; CATALYST LAYER; PERFORMANCE; CARBON; PEMFC; MICROSTRUCTURE; PLATINUM; IONOMER; MEA